2016
DOI: 10.3402/fnr.v60.30955
|View full text |Cite
|
Sign up to set email alerts
|

Toward crustacean without chemicals: a descriptive analysis of consumer response using price comparisons

Abstract: BackgroundTo date, there seems to be limited-to-zero emphasis about how consumers perceive crustacean products subject to either chemical and or non-chemical preservative treatments. In addition, studies that investigated price comparisons of crustacean products subject to either chemical or chemical-free preservative methods seem unreported.ObjectiveThis study focused on providing some foundational knowledge about how consumers perceive traditionally harvested crustaceans that are either chemical-treated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…However, dark discoloration that arises post mortem makes the shrimp unacceptable for purchase by consumers ( 16 ). Previous studies demonstrated that post mortem discoloration could be prevented by pretreating DWRS with various chemical approaches, such as those using chemical antioxidants (e.g., resorcinol, sulfites), melanosis-inhibiting formulations, phenolic extract derived from olive vegetation water, or applying non-thermal processes, such as MAP combined with frozen storage ( 10 , 17 19 ). Quantifying FAAs in fishery products could advance our current understanding of various autolytic processes, as well as muscle degradation, which decisively influences FAA evolution ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, dark discoloration that arises post mortem makes the shrimp unacceptable for purchase by consumers ( 16 ). Previous studies demonstrated that post mortem discoloration could be prevented by pretreating DWRS with various chemical approaches, such as those using chemical antioxidants (e.g., resorcinol, sulfites), melanosis-inhibiting formulations, phenolic extract derived from olive vegetation water, or applying non-thermal processes, such as MAP combined with frozen storage ( 10 , 17 19 ). Quantifying FAAs in fishery products could advance our current understanding of various autolytic processes, as well as muscle degradation, which decisively influences FAA evolution ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%